O ciclo investigativo na promoção do letramento estatístico: um estudo com estudantes do 9º ano do ensino fundamental - Bidin, Monica (2024)
The present work aims to investigate and analyze signs of Statistical Literacy in students based on didactic proposals based on the Investigative Cycle. Aiming to achieve the proposed objective, a bibliographical survey was carried out presenting a mapping through investigations based on theses and dissertations related to the teaching of Statistics in the Final Years of Elementary Education in Basic Education, in the period 2012-2022, in the Theses Catalog and Dissertations from Capes and the Brazilian Digital Library of Theses and Dissertations. In order to detect and understand the investigations carried out involving this topic, approaches and distances were established in the mapped research. The theoretical framework for teaching Statistics is based on the concepts defined by Gal (2002), as well as the Investigative Cycle proposed by Wild and Pfannkuch (1999), with the PPDAC model (Problem, Planning, Data, Analysis and Conclusion). Relevant information for teaching Statistics in Basic Education was considered, proposed in the National Common Curricular Base (BNCC), Brazil, (2018) and in the Guidelines for Assessment and Instruction in Statistics Education (GAISE), Franklin et al. (2005) and Bargagliotti et al. (2020) and on Critical Mathematics Education proposed by Skovsmose (2017) and Alro and Skovsmose (2007). With the intention of developing, implementing and evaluating didactic proposals based on the Investigative Cycle that aim to promote students' Statistical Literacy, a case study research was developed in 2023, in a class of students in the 9th year of Elementary School at State School of Basic Education Professor Cléia Salete Dalberto, located in the municipality of Tenente Portela, Rio Grande do Sul. In this way, it is characterized as a qualitative and case study research, based on didactic proposals based on the Investigative Cycle. Thus, the study aims to answer the following problem: What contributions do teaching proposals, based on the Investigative Cycle, provide to students in the development of Statistical Literacy? To answer this question, the productions of twentythree students were analyzed, guided by the levels of Statistical Literacy proposed by researchers Watson and Callighman (2003). The results of the Pre-Test showed low levels of Statistical Literacy in all questions analyzed, with the highest percentage of students being categorized at the Idiosyncratic level. The highest percentage found in the Post-Test was 87%, in the Inconsistent category. In this context, we believe that through an investigative scenario, students expanded their knowledge regarding the teaching of Statistics in the Final Years of Elementary School.